The Mechanism for the Provision of Advisory Support in the Area of Transport Corridor of Black Sea Economic Cooperation Organization - Alexey Igorevich Bykov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Examines current trends in project implementation, international black sea transport corridor. The conditions of interaction between the member countries of the Organization of the Black Sea Economic Cooperation. Offers directions consulting support during implementation of the project «Black Sea Ring». Discusses the basic components of the mechanism for providing Advisory support in the area of transport corridor of Black Sea Economic Cooperation Organization.